THE EVOLUTION OF THE URDU SHORT STORY: A COMPREHENSIVE ANALYSIS IN SOCIAL, POLITICAL, AND PSYCHOLOGICAL PERSPECTIVES - Abdul Khalique Janwari (Journal of Religion and Society, 2024)
This article presents a comprehensive analysis of the evolution of the Urdu short story through social, political, and psychological perspectives, tracing its development from the late nineteenth century to the contemporary era. The study examines how the Urdu short story emerged as a dynamic literary form that not only reflected but actively engaged with the changing realities of its time. In the social dimension, the analysis explores the transition from Premchand's rural realism and reformist agenda through the progressive writers' focus on class consciousness and gender politics to modernist and postmodernist engagements with urban alienation, consumerism, and identity crisis. The political perspective traces the genre's response to colonialism, the trauma of partition, the oppression of military dictatorships, and the emergence of resistance literature as a powerful voice against tyranny. The psychological dimension investigates the influence of Freudian psychoanalysis, Jungian archetypes, and existential philosophy on characterization and narrative technique, particularly the use of stream of consciousness and internal monologue. The study argues that these three dimensions are not isolated but deeply intertwined throughout the genre's history, collectively shaping the Urdu short story into a comprehensive document of human experience that continues to maintain its creative vitality in contemporary literature. Keywords: Urdu Short Story, Social Realism, Political Resistance, Psychological Narrative, Partition Literature, Literary Evolution